2018
DOI: 10.1158/1940-6207.capr-18-0057
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Alcohol Intake and High-Grade Prostate Cancer: Results from an Equal-Access, Racially Diverse Biopsy Cohort

Abstract: Epidemiologic evidence for an association between alcohol and prostate cancer is mixed. Moreover, there is a lack of research investigating early-life alcohol intake as a risk factor for either overall or high-grade prostate cancer. We examined lifetime alcohol intake in association with prostate cancer diagnosis in an equal-access, racially diverse prostate biopsy cohort. Men undergoing prostate biopsy at the Durham Veterans Affairs Medical Center from 2007 to 2018 completed a survey indicating average number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…So far, epidemiologic evidence for association between alcohol intake and the risk of PCa still remain unclear. Many articles, meta-analyses and systematic reviews showed contradictory conclusions (46)(47)(48)(49). The possible reason might be the gene polymorphism which was associated with the enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…So far, epidemiologic evidence for association between alcohol intake and the risk of PCa still remain unclear. Many articles, meta-analyses and systematic reviews showed contradictory conclusions (46)(47)(48)(49). The possible reason might be the gene polymorphism which was associated with the enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…The latest evidence suggests that there is no safe level of alcohol consumption with regard to health [29]. Heavier alcohol intake earlier in life and higher cumulative lifetime intake were positively associated with high-grade PCa diagnosis [30]; however, this analysis only focused on the alcohol intake 12 mo before RP.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, diverse meta-analyses have found that there is a strong relationship between the amount of alcohol consumed and PCa risk and mortality [ 83 , 91 ]. Moreover, heavier drinking and heavier alcohol exposure earlier in life were shown to be associated with an increased risk of high-grade disease, but had no association with low-grade PCa risk [ 92 , 93 ]. Red wine has been associated with a reduction of PCa risk, especially in more aggressive forms of the disease [ 94 , 95 ].…”
Section: Impact Of Lifestyle On Pca Developmentmentioning
confidence: 99%